Portals of Globalization Repositioning Mumbai's Ports and Zones, 1833-2014 - Maruschke, Megan (Dialectics of the Global, 2019)
This book investigates the planning of Mumbai's ports and free zones, focusing on periods of global and regional change: the early British Raj, independence, and economic liberalization. The port and free zone projects described in this book illustrate how state and non-state actors seek to reposition the city within shifting global, regional, and national frameworks. This history calls master narratives on zones and globalization into question.